The relationship between perceived academic stress and college students’ employment anxiety: the mediating role of psychological resilience - Yang, Mengshan; Li, Xin; Qin, Xiaoye; Tian, Xusheng; Zhang, Hao; Wen, Hongjuan (Frontiers in Psychiatry, 2025)
BackgroundUniversity graduates increasingly face academic and employment-related pressures, particularly in the post-COVID-19 era. Employment anxiety has emerged as a significant mental health issue during the transition from school to work, but its underlying mechanisms remain underexplored.ObjectiveThis study aimed to investigate the mediating role of psychological resilience in the relationship between academic stress and employment anxiety among Chinese undergraduate students.MethodsA cross-sectional survey was conducted among 1124 students from three universities in China. Participants completed validated measures of academic stress, psychological resilience, and employment anxiety. Pearson correlation analysis and mediation testing were performed using PROCESS macro Model 4, with 5000 bootstrap samples.ResultsAcademic stress was positively associated with employment anxiety (B=0.421, p<0.001) and negatively associated with psychological resilience (B=–0.230, p<0.001). Psychological resilience negatively predicted employment anxiety (B= –0.444, p<0.001) and partially mediated the relationship between academic stress and employment anxiety. The indirect effect accounted for 19.50% of the total effect. After controlling for gender, grade, family income, and internship experience, the mediation remained significant and robust.ConclusionPsychological resilience plays a protective mediating role in the link between academic stress and employment anxiety. These findings underscore the importance of enhancing resilience through targeted interventions to reduce employment-related anxiety among university students. Educational institutions should integrate resilience-building strategies into academic and career counseling to promote student mental health and employability.